SOSIALISAI MENGENAI INTERVENSI PENDIDIKAN ANAK BERKESULITAN BELAJAR BAGI GURU SD NEGERI 02 CODO KECAMATAN WAJAK KABUPATEN MALANG - Ruth Rosalia Nababan; Hengky Triwijaya (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2022)
The aim of the Intervention Socialization for Children with Special Learning Difficulties at SDN 02 Codo, Wajak District, Malang Regency is to provide teachers with SDN 02 Codo, Wajak District, Malang Regency about intervention programs for children with special learning difficulties. The target of this program is SDN 02 Codo teachers in Codo Village, Wajak District, Malang Regency. The strategy for implementing the